Implementasi Kurikulum Merdeka dalam Pembelajaran PJOK pada SMP Negeri se-Kecamatan Sape Kabupaten Bima - Saputra, Muchammad Akhsan; Jamaludin, Jamaludin; Irmansyah, Johan; Muslimin, Muslimin (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
The implementation of the Merdeka Curriculum in physical education still faces differences in school readiness, particularly regarding teachers’ understanding, facilities, technology use, and assessment practices. This study aimed to describe the implementation of the Merdeka Curriculum in physical education learning and identify the challenges faced by teachers at public junior high schools in Sape District. A qualitative approach with a case study design was employed in five public junior high schools. The informants included physical education teachers, principals or vice principals for curriculum affairs, and students. Data were collected through semi-structured interviews, classroom observations, and documentation of teaching materials. Data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings showed that the curriculum was implemented through active learning, collaboration, simple projects, and character reinforcement. The main challenges were limited facilities, uneven teacher understanding, limited technology use, and authentic assessment.